Antecedents and Implications of Innovation Capability: Empirical Study of Bakpia MSMEs in Yogyakarta - Baroroh Dwi Nurhayati; Titik Kusmantini; Tri Wahyuningsih (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: This research examines the antecedents and implications of innovation capability, empirically. The outcomes aim at contributing to the knowledge and understanding about the main driver of innovation capability. Background Problems: Yogyakarta is known for its many and varied charms, its tourist attractions, the availability of facilities and infrastructure to support tourism, such as souvenir sellers. But there is known that number of total foreign and domestic tourists has been a decrease in 2018 (Semester I by 11.51% and II by 3.33%), also in 2019 (Semester I by 11.23%). This is a challenge for MSMEs in the tourism sector and MSMEs in other sectors that support tourism, such a souvenir seller. Bakpia is one of the well-known products of the food and beverage sector in Yogyakarta often bought for souvenirs. The Bakpia MSMEs’ innovations were triggered by competition among the Bakpia producers in Yogyakarta. Therefore, every Bakpia MSME must be competitive to survive in the market. Thus, there is a need to improve their innovation capability, which will impact the innovation performance of the Bakpia MSMEs in Yogyakarta. There is a gap in the research regarding the influence of the factors that are predicted to build innovation capability. Novelty: Previous studies’ results indicate that the influence of knowledge donating and knowledge collecting about innovation performance is not yet conclusive. Therefore, this study aims to fill the gap in the previous research by examining the role of capability as a mediating between knowledge sharing process (knowledge donating and knowledge collecting) to innovation performance. Research Methods: Forty-eight items of data were obtained from Bakpia MSMEs in Yogyakarta through a survey conducted by distributing questionnaires directly to them. The data were analyzed using PLS-SEM via SmartPLS version 3.3.2. Findings/Results: This study shows that the direct and indirect effects of sharing knowledge (which includes donating and collecting knowledge) about innovation performance are found to be positive but not significant. The results also indicate that innovation capability does not significantly mediate knowledge donating and knowledge collecting about innovation performance. Meanwhile, the influence of innovation capability on innovation performance was found to be positive and significant. Conclusion: The antecedents are insignificant for innovation capability, but the antecedent’s constructs still act as a driver to build innovation capability.